2007
DOI: 10.1103/physreva.76.062112
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-variable entanglement sharing in noninertial frames

Abstract: We study the distribution of entanglement between modes of a free scalar field from the perspective of observers in uniform acceleration. We consider a two-mode squeezed state of the field from an inertial perspective, and analytically study the degradation of entanglement due to the Unruh effect, in the cases of either one or both observers undergoing uniform acceleration. We find that for two observers undergoing finite acceleration, the entanglement vanishes between the lowest frequency modes. The loss of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
217
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(227 citation statements)
references
References 58 publications
8
217
2
Order By: Relevance
“…The case of continuous variables was studied in Ref. [31], where it was shown that the entanglement is completely destroyed in the limit of infinite acceleration for scalar fields, in contrast to what was found for Dirac ones [32]. In a recent work, two of the present authors observed sudden death of entanglement in a two-qubit system when one of the partners is accelerated by some external agent [33].…”
Section: Introductionmentioning
confidence: 91%
“…The case of continuous variables was studied in Ref. [31], where it was shown that the entanglement is completely destroyed in the limit of infinite acceleration for scalar fields, in contrast to what was found for Dirac ones [32]. In a recent work, two of the present authors observed sudden death of entanglement in a two-qubit system when one of the partners is accelerated by some external agent [33].…”
Section: Introductionmentioning
confidence: 91%
“…(1)). Since the loss of entanglement occurs due to the leakage of information into the inaccessible regions [43,44] as a result of the Unruh effect. The quicker decrease in entanglement with the increasing acceleration arises because the information leakage is higher due to the acceleration of two observers as compare to the case of one accelerated observer.…”
Section: Dynamics Of Tripartite Entanglement In Accelerated Framesmentioning
confidence: 99%
“…Following the pioneering work presented by Peres et al [6], many authors [7][8][9][10][11][12][13][14][15][16][17][18][19] considered the quantum entanglement in a relativistic setting. Recently, Adesso et al [20] discussed the entanglement sharing of a scalar field in the noninertial frame and found that the classical correlation is independent of the acceleration of the observer if the other observer stays stationary. Juan Len et al studied the Dirac entanglement in both the spin and occupation number cases [21], and Mann et al discussed the speeding up entanglement degradation of the scalar field in the noninertial frame [22].…”
Section: Introductionmentioning
confidence: 99%